Effect of irradiation and deuterium behavior in Li-based tritium breeding ceramics - Karpov, S.; Ruzhytskyi, V.; Tolstolutska, G.; Rostova, H. (Вопросы атомной науки и техники, 2022)
The behavior of implanted deuterium in advanced lithium orthosilicate (Li₄SiO₄) pellets with addition of lithium metatitanate (Li₂TiO₃), and in reference Li₄SiO₄ pellets, has been investigated. Thermal desorption (TD) spectroscopy was used to study the deuterium interaction with radiation defects in materials. Computational evaluation of deuterium desorption within the framework of the diffusion-trapping model allowed to associate characteristics of experimental TD spectra with specific trapping sites in the material. It was found that deuterium desorption is limited mainly by intragranular diffusion of deuterium and its trapping by radiation defects associated with Li-vacancy traps. Deuterium gas release from both ceramics demonstrated similar trend indicating weak dependence of deuterium trapping behavior on phase composition. The change of the morphology and elemental composition of the pellets surface has been analyzed. SEM examination indicated that ion irradiation and subsequent thermal desorption annealing of two-phase ceramics leads to an increase in surface destruction processes.